Nonuniform C-Band Loop Antenna: A New Approach for Future UWB Applications - Shastri, S. P. R.; Singh, R. R.; Ajetrao, K. V. (Engineering, Technology & Applied Science Research, 2018)
Antenna design becomes very difficult at very small wavelengths and a special lab is required to manufacture a small antenna which costs a lot. A new approach is proposed to enhance the bandwidth of the loop antenna which can be designed at very high frequency using conventional PCB design. The proposed antenna is a nonuniform loop and covers UWB frequency range. The nonuniform structure of the loop is designed using the concept of both thin and thick loop antenna together which leads to an improvement in the antenna bandwidth. The proposed nonuniform loop antenna covers a band of 91.4% which is higher than any existing printed loop antenna. The frequency ranges from 3.54GHz to 9.5GHz and the measured result is in agreement with the simulated result. This technique can be very helpful in designing UWB antennas in the range of Ku or higher than this.